Participation in Christ and Divine and Human Righteousness: Reading Paul with Gregory of Nyssa - Heavin, Joshua (2025)
Participation in Christ and divine and human righteousness are vital, yet perennially debated, Pauline motifs. Arguably, what is most distinctive and crucial about ‘righteousness’ in Paul's epistles is its christological re-definition in texts such as 1 Cor 1:30. I contend Gregory of Nyssa's theological interpretation of the Apostle Paul is a generative resource for understanding participation in Christ and inter-relating divine and human righteousness. After sketching four crucial aspects of participation in Nyssen's broader theological vision, I explore three instances where Nyssen contemplates the meaning of righteousness and participation in 1 Cor 1:30, and explore their contribution for reading Paul today.